Simbología animal entre cuentos de Monterroso y Haqqi : studio comparado - Rawan Ibrahim Abdelmawgod Ibrahim; Mariam Bourhan Eldin (2022)
. . . . . . . . . . .
Thesis (M.Sc.)-Cairo University - Faculty of Arts - Department of Spansh
Bibliography: p. 127-138.
Keywords: Spanish Arts; Yahya Haqqi